2020
DOI: 10.1002/jper.20-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peri‐implant infection on serum biochemical analysis

Abstract: Background: Peri-implant disease (PID) has not been directly linked to pathological organ changes. The present study assessed the dynamics of serum biochemical parameters in a model of experimental peri-implantitis in dogs, followed by open flap debridement. Methods: Seven male beagle dogs comprised the study group. Procedures were performed as follows-extractions of two premolars and one molar on each mandibular quadrant (Day 0); bone healing time (week14); placement of four rough-surface endoosseous implants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
(89 reference statements)
1
15
0
Order By: Relevance
“…A linear correlation was also found between clinical peri-implant inflammatory parameters and WBC levels. Along similar lines, recent animal studies have shown an increased systemic inflammatory response after ligature-induced experimental peri-implantitis that was characterized by high levels of total protein, albumin, and WBC, which reverted to baseline after surgical peri-implant treatment [ 7 8 ]. The systemic inflammatory state of peri-implantitis patients was confirmed by lower circulating levels of IL-10, a cytokine with important anti-inflammatory properties [ 15 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A linear correlation was also found between clinical peri-implant inflammatory parameters and WBC levels. Along similar lines, recent animal studies have shown an increased systemic inflammatory response after ligature-induced experimental peri-implantitis that was characterized by high levels of total protein, albumin, and WBC, which reverted to baseline after surgical peri-implant treatment [ 7 8 ]. The systemic inflammatory state of peri-implantitis patients was confirmed by lower circulating levels of IL-10, a cytokine with important anti-inflammatory properties [ 15 ].…”
Section: Discussionmentioning
confidence: 95%
“…Recent animal studies have shown elevation of peripheral levels of pro-inflammatory biomarkers (e.g., total protein, albumin, and white blood cells [WBC]) after ligature-induced experimental peri-implantitis [ 7 8 ]. It is worth mentioning that the surgical treatment of experimental peri-implantitis by means of open flap debridement led to a reduction of these systemic inflammatory parameters, which reached similar values to baseline [ 7 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ACD is considered to be mediated by cytokines that are produced as a consequence of the inflammatory process, we can hypothesize that peri-implant disease may affect blood count through a cytokine-mediated mechanism and speculate that a similar mechanism is plausible for other systemic conditions. Actually, serum inflammatory markers resulted higher in dogs with experimental peri-implantitis in another study by the same authors [ 39 ]. One recent human study reinforced this evidence, finding that common CVD markers such as triglycerides, uric acid, and white blood cells were significantly higher in patients with peri-implantitis [ 40 ].…”
Section: Discussionmentioning
confidence: 98%
“…A second study by Chaushu et al [ 39 ] explored the dynamics of serum biochemical parameters following experimental peri-implantitis in a dog model. The authors noted an increase in inflammatory parameters such as total protein and albumin concentrations.…”
Section: The Impact Of Peri-implantitis On Systemic Conditionsmentioning
confidence: 99%